Vaccination with a live multi-gene deletion strain protects horses against virulent challenge with Streptococcus equi. Issue 9 (25th February 2015) - Robinson, Carl; Heather, Zoe; Slater, Josh; Potts, Nicola; Steward, Karen F.; Maskell, Duncan J.; Fontaine, Michael C.; Lee, Jeong-Jin; Smith, Ken; Waller, Andrew S.
Graphical abstract: Highlights: A Streptococcus equi vaccine strain containing deletions in six genes was generated. Intramuscular vaccination protected 85% of ponies from strangles. Vaccinated ponies did not seroconvert to SeM, suggesting that this test could be used as a differential diagnostic. Adverse reactions occurred in five of nine vaccinated ponies. Abstract: Strangles, caused by Streptococcus equi subspecies equi ( S. equi ) is one of the most frequently diagnosed infectious diseases of horses and there remains a significant need to develop new preventative vaccines. We generated a live vaccine strain of S. equi containing deletions in six genes: sagA, hasA, aroB, pyrC, seM and recA, which was administered to nine Welsh mountain ponies via the intramuscular route. Four vaccinated ponies developed adverse reactions following the first vaccination from which the live vaccine strain was isolated. Two of these ponies were withdrawn from the study and seven ponies received a second vaccination, one of which then developed an adverse reaction. Nine control ponies injected with culture media alone developed no adverse reactions. Following challenge with a virulent strain of S. equi, none of the seven vaccinated ponies had developed clinical signs of strangles eleven days post-challenge, compared to six of nine control ponies over the same period ( P  = 0.0114). A lymph node abscess was identified in one of the seven vaccinated ponies at post-mortem examination, whilst all nine control ponies had at least one lymph node abscess ( P  = 0.0009). Three of the six vaccinated ponies that were protected from strangles had not developed an adverse reaction following vaccination, suggesting that a better understanding of the pro-inflammatory responses to S. equi could lead to the development of a live attenuated vaccine against strangles that is safe for administration via intramuscular injection.